Pengaruh Islamic Financial Literacy, Financial Knowledge dan Financial Attitude Terhadap Financial Management Behavior (Studi Pada Santri Pondok Pesantren Sabilurrosyad Malang) - Nadziroh, Umi Aimmatun; Malikah, Anik; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract In the modern era, consumption patterns have undergone significant changes, particularly among young generations, including students in Islamic boarding schools (Pesantren). One of the crucial factors influencing consumer behavior is financial management behavior, which plays a vital role in maintaining financial stability. This study aims to identify the partial influence of Islamic financial literacy, financial knowledge, and financial attitude on financial management behavior at Pondok Pesantren Sabilurrosyad Malang. This research employs a quantitative method, with data collected using a purposive sampling technique. The sample size was determined using the Slovin formula, resulting in 177 respondents, all of whom are active students. The data were analyzed using multiple linear regression with SPSS 25 software. The findings indicate a significant positive effect of Islamic financial literacy, financial knowledge, and financial attitude on financial management behavior at Pondok Pesantren Sabilurrosyad Malang. Additionally, each of the variables Islamic financial literacy, financial knowledge, and financial attitude has a partial influence on financial management behavior at Pondok Pesantren Sabilurrosyad Malang. Keywords: Islamic Financial Literacy, Financial Knowledge, Financial Attitude, Financial Management Behavior.